Proton motive force in growing Streptococcus lactis and Staphylococcus aureus cells under aerobic and anaerobic conditions. - Kashket, E R (1981)
Measurements of the electrochemical gradient of hydrogen ions, which gives rise to the proton motive force (PMF), were carried out with growing Streptococcus lactis and Staphylococcus aureus cells. The facultative anaerobe was chosen in order to compare the PMF of cells growing aerobically and anaerobically. It was expected that during aerobic growth the cells would have a higher PMF than during anaerobic growth, because the H+-translocating ATPase (BF0F1) operates in the direction of H+ influx and ATP synthesis during respiration, whereas under anaerobic conditions the BF0F1 hydrolyzes glycolytically generated ATP and establishes the proton gradient by extruding H+. The electrical component of the PMF, delta psi, and the chemical gradient of H+, delta pH, were measured with radiolabeled tetraphenylphosphonium and benzoate ions. In both S. lactis and S. aureus cells, the PMF was constant during the exponential phase of batch growth and decreased in the stationary phase. In both species of bacteria, the exponential-phase PMF was not affected by varying the growth rate by adding different sugars to the medium. The relative contributions of delta psi and delta pH to the PMF, however, depended on the pH of the medium. The internal pH of S. aureus was constant at pH 7.4 to 7.6 under all conditions of growth tested. Under aerobic conditions, the delta psi of exponential phase S. aureus remained fairly constant at 160 to 170 mV. Thus, the PMF was 250 to 270 mV in cells growing aerobically in media at pH 6 and progressively lower in media of higher pH, reaching 195 to 205 mV at pH 7. Under anaerobic conditions, the delta psi ranged from 100 to 120 mV in cells at pH 6.3 to 7, resulting in a PMF of 150 to 140 mV. Thus, the mode of energy metabolism (i.e., respiration versus fermentation) and the pH of the medium are the two important factors influencing the PMF of these gram-positive cells during growth.